2018
DOI: 10.2106/jbjs.cc.18.00114
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Terrible Triad Injury of the Elbow: A Rare and Easily Missed Injury

Abstract: Case: We report the case of a pediatric terrible triad injury of the elbow consisting of an ulnohumeral dislocation, a radial neck fracture, and a coronoid chondral injury, which was diagnosed at 14 days following injury. We describe our surgical technique and provide details of the postoperative course, including the development of a rotational contracture following heterotopic ossification. Conclusion: We describe a rare and challenging injury that sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Rooke et al reported a terrible triad injury in a 12-year-old boy characterized by elbow dislocation, radial neck fracture, and displaced coronoid chondral fragment. While the classic definition of terrible triad entails radial head and coronoid process fracture, these fractures were not exactly those that were seen in the study of Rooke et al 5 Dailiana et al also reported two cases as pediatric terrible triad injuries, while commentators suggested these cases cannot be even regarded as a variant of terrible triad because one of them had no elbow dislocation in the radiographic evaluation and the other one was a transolecranon fracture-dislocation. 6 In the present study, we reported a case with the elbow dislocation, radial head fracture, and displaced coronoid chondral fragment.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Rooke et al reported a terrible triad injury in a 12-year-old boy characterized by elbow dislocation, radial neck fracture, and displaced coronoid chondral fragment. While the classic definition of terrible triad entails radial head and coronoid process fracture, these fractures were not exactly those that were seen in the study of Rooke et al 5 Dailiana et al also reported two cases as pediatric terrible triad injuries, while commentators suggested these cases cannot be even regarded as a variant of terrible triad because one of them had no elbow dislocation in the radiographic evaluation and the other one was a transolecranon fracture-dislocation. 6 In the present study, we reported a case with the elbow dislocation, radial head fracture, and displaced coronoid chondral fragment.…”
Section: Discussionmentioning
confidence: 89%
“…Correspondence to Danial Hosseinzadeh, MD, Shafa Orthopedic Hospital, Baharestan Square, Tehran, Iran Tel: +98(21)33542000-8; Fax: +98(21)33542020; e-mail: danyal_h1984@yahoo.com. literature, 5,6 all of which seem more like a variant of the terrible triad instead of classically defined terrible triad injury. Rooke et al reported a terrible triad injury in a 12-year-old boy characterized by elbow dislocation, radial neck fracture, and displaced coronoid chondral fragment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from each study in group 1 are summarized in Table II. Rooke et al 29 described a case of a 12-year-old boy who presented to the ED after a fall from his bicycle. He was initially diagnosed with a Salter-Harris type 2 fracture of the proximal radius.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Terrible Triad VariantsFour of the 19 included articles described variants of the typical TTE. Group 2 had a total of four patients (three males and one female) with a mean age of 22.35 years old (range[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Patient characteristics, MOI, TTE variant, and other injuries for each study are described in TableIII.J o u r n a l P r e -p r o o fTerrible Triad of the Elbow and Associated Variants Desai et al7 reported the case of a 25-year-old polytrauma patient who sustained a TTE variant consisting of a posterior elbow dislocation, coronoid process, and capitellum fractures.…”
mentioning
confidence: 99%